2023
DOI: 10.1111/gcb.17001
|View full text |Cite
|
Sign up to set email alerts
|

Managing mineral phosphorus application with soil residual phosphorus reuse in Canada

Jiaxin Wang,
Zhiming Qi,
Elena M. Bennett

Abstract: With limited phosphorus (P) supplies, increasing P demand, and issues with P runoff and pollution, developing an ability to reuse the large amounts of residual P stored in agricultural soils is increasingly important. In this study, we investigated the potential for residual soil P to maintain crop yields while reducing P applications and losses in Canada. Using a P cycling model coupled with a soil P dynamics model, we analyzed soil P dynamics over 110 years across Canada's provinces. We found that using soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 132 publications
(198 reference statements)
0
2
0
Order By: Relevance
“…In this study, the alternation in soil total phosphorus levels after the forest-to-cropland conversion was suggested to be the main reason for the decline of the cropland-declined microbial cluster (Figures d and S7). This was not surprising because people may apply excessive phosphorus fertilizer into the soils during agricultural practices, which might have adverse effects on certain microbial taxa, especially those within the cropland-declined microbial cluster. For instance, it was reported that soils with higher P levels were not conducive to the growth and activity of Candidatus Solibacter genus (i.e., the keystone taxon within the co-occurrence and coexclusion network herein) .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the alternation in soil total phosphorus levels after the forest-to-cropland conversion was suggested to be the main reason for the decline of the cropland-declined microbial cluster (Figures d and S7). This was not surprising because people may apply excessive phosphorus fertilizer into the soils during agricultural practices, which might have adverse effects on certain microbial taxa, especially those within the cropland-declined microbial cluster. For instance, it was reported that soils with higher P levels were not conducive to the growth and activity of Candidatus Solibacter genus (i.e., the keystone taxon within the co-occurrence and coexclusion network herein) .…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining appropriate P levels in the soil is crucial to prevent eutrophication and ensure efficient P utilization . The latest strategies for sustainable P use involve P mineralization, which helps balance effective P activity through the in situ formation of slow-release P pools, e.g., hydroxyapatite, struvite, and Fe- and Al-phosphorus oxide. Currently, there is limited research on the intricate interplay mechanisms and synergism of F and P in the environment. Fluorapatite (FAP) is a natural mineral that contains both F and P .…”
Section: Introductionmentioning
confidence: 99%